Book Review of Understanding Social Justice in Rural Education by H. Cuervo - Michael Corbett (Journal of Research in Rural Education, 2017)
A number of books on the subject of rural education have appeared recently. Several are excellent and serve to move the fi eld in a positive direction by taking up questions which have been present in the rural education literature for some time, but which have not had the kind of in-depth treatment aff orded by a book-length study. Notable here are several titles. In Why Rural Schools Matter (2014), Mara Tieken deals principally with racial diversity in rural schooling, but simultaneously with the more traditional rural education preoccupation with understanding the importance of schools in rural locations. Jinting Wu's Fabricating an Educational Miracle (2016) is a broadly theorized study of the complex interface of education, mobility, development, and audit culture in rural China. Wendy Geller's (2015) Rural Young Women, Education, and Socio-Spatial Mobility is an analysis of the educational decision making of young women in rural areas in which she engages with contemporary literatures concerning mobilities, gender, and identity formation.